2000
DOI: 10.1111/1468-0351.00045
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Impacts of the 1998 Financial Crisis in Russia and the Response of the Public Safety Net

Abstract: We compare welfare indicators for a nationally-representative sample of Russians interviewed shortly after the 1998 financial crisis with data on the same people two years earlier. Both objective and subjective measures reveal a widespread, though not universal, deterioration in welfare. Current expenditures generally contracted more than incomes. Inequality fell. There were both gainers and losers at all levels. The safety net's response fell far short of what was needed to protect living standards, but it di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 11 publications
1
70
0
1
Order By: Relevance
“…In order to evaluate poverty one needs to define a financial satisfaction level below which an individual is considered poor. Besides the financial satisfaction question, there are also other subjective questions that have been used to evaluate the incidence of poverty, notably the Income Evaluation Question (Goedhart et al 1977) and the Economic Ladder Question (Ravallion and Lokshin 1999;Lokshin and Ravallion 2000).…”
Section: Valuation Studies and Welfare Analysismentioning
confidence: 99%
“…In order to evaluate poverty one needs to define a financial satisfaction level below which an individual is considered poor. Besides the financial satisfaction question, there are also other subjective questions that have been used to evaluate the incidence of poverty, notably the Income Evaluation Question (Goedhart et al 1977) and the Economic Ladder Question (Ravallion and Lokshin 1999;Lokshin and Ravallion 2000).…”
Section: Valuation Studies and Welfare Analysismentioning
confidence: 99%
“…Lokshin and Ravallion (2000), examining the welfare effects of the 1998 financial crisis, find that it was not felt only by those poor prior to 1998 but impacted upon individuals across the income distribution. Analysing the effects of changes in the distribution of social welfare spending they find that social policy was "on balance, poverty reducing".…”
Section: [Table 1 Here]mentioning
confidence: 99%
“…Ligon and Schechter (2003) measure vulnerability as the difference between the utility associated with some certainty-equivalent consumption and the expected utility defined according to realized consumption. c) Vulnerability as uninsured exposure to risk provides an alternative ex post assessment of welfare loss arising from the onset of an economic shock (Glewwe and Hall (1998), Maloney et al (2004) and Lokshin and Ravallion (2000) all offer analysis using this approach). In this paper we utilise the latter empirical category centring on the observed effects of uninsured risk exposure or the inability to effectively manage risk when subjected to shocks.…”
Section: The Concept Of Vulnerability and The Theoretical Frameworkmentioning
confidence: 99%
“…Milanovic (2000) looked at social protection transfers in Latvia and found a weak pro-poor role of social protection benefits. Lokshin and Ravallion (2000) analyzed the role of the social safety net in protecting the poor from the 1998 Russian financial crisis and concluded that the social safety net in place was largely insufficient to protect the poor from the Russian crisis. Ravallion et al (1995) looked at the early years of the transition in Hungary and found that the safety net was able to protect effectively from poverty but did not play an important role in lifting people out of poverty.…”
Section: Some Evidence On Public and Private Transfers In Transitionmentioning
confidence: 99%